Pemikiran Al-Maturidiyah Dalam Pemikiran Islam - Abu Zar (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2014)
Matudiridyah was known as a moderat school that aims to elaborate between the Mu’tazilah and Asyariyah School. It was established by its founder Abu Manshur al-Maturidi. Amongst the crucial Islamic thought, Abu Manshur stood out to introduce a new paradigm of Islamic theology. He aimed at bridging the two contradicting Islamic theology school between Asyari and Mu’tazilah. However, his effort was not running well due to Maturidiyah School came to frictions namely Samarkand and Bukhari. The Samarkand school tended to be in line with Mu’tazilah thought, while the later tended to support Asyariyah theology.